The Attitudes of Jordanian Elites about the Coverage of News Websites to Current Political Events: A Field Study - Alawneh, Hatem; Nejadat, Ali; Alkadi , Amjad (Dirasat: Human and Social Sciences, 2023)
The study aimed at identifying the nature of the attitudes of Jordan elites regarding the coverage of news websites regarding current political events and revealed their motives to view/follow these websites. Moreover, the study was interested to know the major current political events which deserve to be viewed /followed by the population of the study. To achieve the objectives of the study, the researchers embarked upon the nature of descriptive studies, within the framework of which, the survey method was used by applying the method of surveying the population by sample. The questionnaire was distributed to (200) Jordan elites representing Academic and Media professionals, who were randomly selected. The study concluded the following major findings: 1. (46.5%) of the population of the study largely view/follow the current political events on electronic news websites. 2. The findings confirmed that the events of Deal of the Century and its repercussions occupied the first grade by (12.9%) followed by the Iraqi crisis, which occupied the second grade by (10.5%). 3. (42.6%) of Jordan elites prefer to view/follow the current political events via foreign Arabic-speaking electronic news websites. 4. The confidence demonstrated by Jordan elites about the effectiveness of coverage of news websites to current political events was medium. 5. The phrase “The coverage of news websites to current political events that cleared my ambiguity and misconception concerning some issues” occupied the first grade on the list of attitudes of Jordan elites regarding the coverage of news websites to current political events.